Shi‘i religious thinkers and the issue of Apostasy - G. R. Nuei; Faisal Ahmad Shah (Malala)
‘Apostasy’ is one of the controversial issues in the Muslim world. According to Islamic teachings, an apostate must be killed. This article is to assess the status of killing fatwas among contemporary Islamic thinkers in general and two Shi‘i religious thinkers in particular. Mohsen Kadivar and Fazil Lankarani have presented differing ideas dealing with the killing of an Azerbaijani journalist, Rafiq Tağı, who was accused of apostasy.